Determining the optimal dose of virginiamycin for ruminal parameters and performance of Nellore cattle on pasture - Neto, João Alexandrino Alves [UNESP]; De Oliveira, Ivanna Moraes [UNESP]; Moretti, Matheus Henrique; Gonçalves, Paloma Helena [UNESP]; Alves, Michele Aparecida Prado; De Resende Fernandes, Juliano José; De Resende, Flávio Dutra [UNESP]; Siqueira, Gustavo Rezende [UNESP] (Universidade Estadual de Londrina, 2018)
There are no studies evaluating the virginiamycin (VM) doses under tropical conditions. So, the present study was conducted to evaluate the optimal dose of VM for growing Nellore bulls on tropical pasture. Two experiments were conducted. The frst experiment, one hundred and two Nellore bulls (307 ± 25 kg body weight [BW]; 22 months) were used. Animal performance was evaluated using a randomized block design, with group as experimental unit (n = 8; 12 animals each). The second experiment, a double 4 × 4 Latin square, eight animals were used to evaluate the ruminal parameters. Four doses were evaluated: 0, 35, 55, and 75 mg VM per 100 kg BW. The average daily gain (P = 0.08) and carcass gain (P = 0.05) exhibited a trend of quadratic behavior. An increased dose of VM did not affect supplement intake (P = 0.64), rumen pH (P = 0.96), acetate: propionate ratio (P = 0.73), or the total concentration of volatile fatty acid (P = 0.63). The concentration of rumen ammonia nitrogen exhibited a quadratic effect (P = 0.01). A quadratic behavior was found for volatile fatty acid, except for propionate, which presented linear behavior (P = 0.03). In conclusion, the dose of 47 mg VM per 100 kg BW is recommend for growing Nellore bulls on tropical pasture.
Keywords: Additive; Non-ionophores; Supplement intake; Tropical grass